Microglial Metabolism After Pediatric Traumatic Brain Injury – Overlooked Bystanders or Active Participants? - Shi, Aria C.; Rohlwink, Ursula; Scafidi, Susanna; Kannan, Sujatha (Frontiers in Neurology, 2021)
Microglia play an integral role in brain development but are also crucial for repair and recovery after traumatic brain injury (TBI). TBI induces an intense innate immune response in the immature, developing brain that is associated with acute and chronic changes in microglial function. These changes contribute to long-lasting consequences on development, neurologic function, and behavior. Although alterations in glucose metabolism are well-described after TBI, the bulk of the data is focused on metabolic alterations in astrocytes and neurons. To date, the interplay between alterations in intracellular metabolic pathways in microglia and the innate immune response in the brain following an injury is not well-studied. In this review, we broadly discuss the microglial responses after TBI. In addition, we highlight reported metabolic alterations in microglia and macrophages, and provide perspective on how changes in glucose, fatty acid, and amino acid metabolism can influence and modulate the microglial phenotype and response to injury.